2023
DOI: 10.1021/acs.jmedchem.3c00554
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the Potent and Selective Inhaled Janus Kinase 1 Inhibitor AZD4604 and Its Preclinical Characterization

Magnus Nilsson,
Kristina Berggren,
Susanne Berglund
et al.

Abstract: JAK-STAT cytokines are critical in regulating immunity. Persistent activation of JAK-STAT signaling pathways by cytokines drives chronic inflammatory diseases such as asthma. Herein, we report on the discovery of a highly JAK1-selective, ATP-competitive series of inhibitors having a 1000-fold selectivity over other JAK family members and the approach used to identify compounds suitable for inhaled administration. Ultimately, compound 16 was selected as the clinical candidate, and upon dry powder inhalation, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…The initial Campaign 1c manufacturing route to supply up to 1 kg of amino acid 4 in support of preclinical studies is shown in Scheme . This route started with the cheap and readily available methyl acrylate ( 5 ), which readily underwent bromination to provide intermediate dibromo-ester 6 . This ester was converted to the corresponding methyl ether 7 by reaction with sodium methoxide (NaOMe) in MeOH.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial Campaign 1c manufacturing route to supply up to 1 kg of amino acid 4 in support of preclinical studies is shown in Scheme . This route started with the cheap and readily available methyl acrylate ( 5 ), which readily underwent bromination to provide intermediate dibromo-ester 6 . This ester was converted to the corresponding methyl ether 7 by reaction with sodium methoxide (NaOMe) in MeOH.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Despite extensive investigations into the optimization of SFC for this purification, the method was found to suffer from low throughput and high solvent (MeOH) consumption. Also, the resolved amino acid was found to form a stable carbonate salt 10 under the chromatography conditions. Subsequent treatment of carbonate salt 10 with aqueous hydrochloric acid (HCl) allowed for isolation of the corresponding crystalline hydrated dihydrochloride salt of amino acid 4 (Scheme ). The dihydrochloride salt was successfully used in subsequent amide formation to eventually afford AZD4604.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This could probably be explained by a broader spectrum of actions of JAK inhibitors, given the role of JAK-1 and JAK-2 in the signaling of different cytokines involved in AD and psoriasis pathogenesis. Regarding atopic comorbidities, limited data are available on the possible role of JAK inhibitors in patients with concomitant asthma or allergic rhinitis [ 28 ]. Few trials are ongoing with topical JAK-1 inhibitors in patients affected by asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Few trials are ongoing with topical JAK-1 inhibitors in patients affected by asthma. As a matter of fact, JAK-1-selective inhibitors that could be used via dry powder inhalation in patients with asthma are currently under evaluation [ 28 ]. In this setting of Th2-mediated asthma, JAK-1 inhibition seems to be more efficacious than JAK-3 inhibition [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation